The influence of self efficacy and motivation on work readiness among students in the office administration education program at Surabaya State University - Meylina Puspitaningsih; Ruri Nurul Aeni Wulandari (Universitas Nusa Cendana, 2026)
This study aims to analyze the role of self-efficacy and motivation in shaping students’ work readiness. A quantitative approach with an explanatory design was used to test the causal relationships among the variables. The study population consisted of 189 students from the 2022 cohort of the Office Administration Education Program at Surabaya State University, with a sample of 128 respondents selected through proportional random sampling. Data collection was conducted using an online Likert-scale questionnaire, which was then analyzed using multiple linear regression with SPSS version 25. The results indicate that self-efficacy and motivation have a positive and significant effect on work readiness, both partially and simultaneously, with a combined contribution of 63.5%. These findings confirm that belief in one’s own abilities and internal motivation play a crucial role in preparing students to enter the workforce. A limitation of this study lies in the limited scope of the respondents; therefore, further research is recommended to involve a broader sample and relevant additional variables. Keywords: Self Efficacy; Motivation; Work Readiness; Students; Office Administration Education